2006
DOI: 10.1038/sj.emboj.7601108
|View full text |Cite
|
Sign up to set email alerts
|

A structural model for monastrol inhibition of dimeric kinesin Eg5

Abstract: Eg5 or KSP is a homotetrameric Kinesin-5 involved in centrosome separation and assembly of the bipolar mitotic spindle. Analytical gel filtration of purified protein and cryo-electron microscopy (cryo-EM) of unidirectional shadowed microtubule-Eg5 complexes have been used to identify the stable dimer Eg5-513. The motility assays show that Eg5-513 promotes robust plus-end-directed microtubule gliding at a rate similar to that of homotetrameric Eg5 in vitro. Eg5-513 exhibits slow ATP turnover, high affinity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
61
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 55 publications
8
61
2
Order By: Relevance
“…1B). Previous moderate resolution (25-30 Å) cryo-EM studies of K5 showed no such rotation upon binding ATP analogues (27,28). However, at these lower resolutions, it has been demonstrated that it would not technically be possible to visualize such movements (49).…”
Section: Subnanometer Resolution Reconstructions Of the Human K5mentioning
confidence: 96%
See 1 more Smart Citation
“…1B). Previous moderate resolution (25-30 Å) cryo-EM studies of K5 showed no such rotation upon binding ATP analogues (27,28). However, at these lower resolutions, it has been demonstrated that it would not technically be possible to visualize such movements (49).…”
Section: Subnanometer Resolution Reconstructions Of the Human K5mentioning
confidence: 96%
“…The first, cryoelectron microscopy (cryo-EM) and image reconstruction, is ideally suited to examine the structure of large complexes and has allowed us to determine the MT-bound structures of human K5 MD at successive steps in its ATPase cycle. Although prior intermediate resolution (ϳ25-30 Å) cryo-EM studies of human K5-MT complexes provided initial insight into the function of these motors (27,28), the movements of individual components of the MD could not been visualized. Our subnanometer resolution reconstructions now enable us to visualize coupled, nucleotide-dependent conformational transitions of human K5 structural elements, including those in L5, the NL, and the N terminus.…”
mentioning
confidence: 99%
“…However, the affinity of Eg5-513 for AMP is so weak that apyrase treatment effectively generates a nucleotide-free state for Eg5 (data not shown). Apyrase-treated Eg5-513 was fully active based on MT binding (34) and steady-state ATP turnover (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, previous analysis of dimeric Eg5, Eg5-513, has indicated that two conjoined motor domains exhibit cooperativity in vitro (34,35). In comparison to a single Eg5 motor domain, the steady-state ATPase of Eg5-513 is reduced 10-fold suggesting the physical attachment of two motor domains causes a reciprocal modulation of each enzymatic cycle (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation